Psychosocial Interventions for People With Both Severe Mental Illness and Substance Misuse - Hunt, Glenn E. (Oxford University Press, 2014)
Over 50% of people with a severe mental illness also use illicit drugs and/or alcohol at hazardous levels. This review is based on the findings of 32 randomized controlled trials which assessed the effectiveness of psychosocial interventions, offered either as one-off treatments or as an integrated or nonintegrated program, to reduce substance use by people with a severe mental illness. The findings showed that there was no consistent evidence to support any one psychosocial treatment over another. Differences across trials with regard to outcome measures, sample characteristics, type of mental illness and substance used, settings, levels of adherence to treatment guidelines, and standard care all made pooling results difficult. More quality trials are required that adhere to proper randomization methods; use clinically valuable, reliable, and validated measurement scales; and clearly report data, including retention in treatment, relapse, and abstinence rates. Future trials of this quality will allow a more thorough assessment of the efficacy of psychosocial interventions for reducing substance use in this challenging population.